2005
DOI: 10.1093/pcp/pci209
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase Activity of the Photosystem II OEC33 Protein from Pea

Abstract: The purpose of this study was to identify the location of one of the two sources of carbonic anhydrase (CA) activity associated with the PSII complex in chloroplast membranes. We tested the hypothesis that the extrinsic 33 kDa protein, OEC33, associated with the oxygen-evolving complex (OEC), is one source of CA activity. We found that precursor OEC33 expressed in Escherichia coli exhibits CA activity, but the expressed precursors of OEC24 or OEC17 do not. The CA activity of OEC33 remained after treatment at 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…S4). Mn 2ϩ binding to PsbO has indeed been demonstrated previously in isolated PsbO from higher plants (72)(73)(74). As in the present study and Ref.…”
Section: Quantification Of the Relative Concentrations Of Ps Ii-boundsupporting
confidence: 89%
See 1 more Smart Citation
“…S4). Mn 2ϩ binding to PsbO has indeed been demonstrated previously in isolated PsbO from higher plants (72)(73)(74). As in the present study and Ref.…”
Section: Quantification Of the Relative Concentrations Of Ps Ii-boundsupporting
confidence: 89%
“…51, protein-bound Mn 2ϩ did not show a CW EPR signal, but a six-line signal was observed after denaturation of the protein (73). PsbO was reported to show carbonic anhydrase activity, which was maximal in the presence of Mn 2ϩ (74 here (see supplemental data and Ref. 61).…”
Section: Quantification Of the Relative Concentrations Of Ps Ii-boundmentioning
confidence: 65%
“…A low level of carbonic anhydrase (CA) activity, more than 10 3 slower than typical Zn 2+ -CA, has been found to be intrinsic to oxygenevolving PS II membranes [69,70]. A soluble CA activity was found associated with the 33 kDa extrinsic protein of PS II (PsbO) and depends on the concentration of Mn 2+ and Cl − .…”
Section: Bicarbonate Ion-bicarbonatementioning
confidence: 99%
“…While CA activity was observed in the manganese-stabilizing protein of the oxygen-evolving complex (PsbO), the recombinant PsbO protein produced in Escherichia coli had no activity without the metal in the active center. When metal ions were added, the highest activity was observed in the presence of manganese ions, while it was much lower in the presence of zinc (Lu et al 2005). It was also found that three proteins from the oxygen-evolving complex possessed CA activity in the presence of manganese ions, but not zinc (Shitov et al 2009).…”
Section: Introductionmentioning
confidence: 97%